Representation of the visual field in the occipital striate cortex. Issue 3 (March 1994) - McFadzean, R; Brosnahan, D; Hadley, D; Mutlukan, E
Abstract : The representation of the field of vision in the human striate cortex is based on the Holmes map in which about 25% of the surface area of the striate cortex is allocated to the central 15 degrees of vision. Following the introduction of computed tomography of the brain, the accuracy of the Holmes map was apparently confirmed by clinical/radiological correlation, but a revision has been proposed by Horton and Hoyt based on a magnetic resonance imaging study of three patients with visual field defects due to striate lesions. They propose that the central cortical representation of vision occupies a much larger area. This study reviews the perimetric and imaging findings in a larger series of patients with striate cortical disease and provides support for the revised representation. The clinical phenomenon of macular sparing and its relation to representation of the macula at the occipital pole is also discussed.